Nutmeg Pulp Herbal Tea Produced Using Shredding Method - Asbahrul Amri; Devi Satria Saputra; Ria Darma (Jurnal Inotera, 2018)
The existing nutmeg pulp herbal tea is produced from slice process which resulted with hard and big particle size of the powder. It is estimated to negatively affect the packaging process and defective product might be possible to occur when distribution taking place. Consequently, the study need to be done to produce nutmeg pulp herbal tea with small particle size of the powder using shredding method and define one of its substance quantity, Vitamin C as the comparable data towards the existing nutmeg pulp herbal tea product. The study reveals that the tea powder produced from shredding method is greatly smaller than slice method. Idiometri titration analysis of 5 nutmeg pulp herbal tea produced from shredding method samples shows that the average quantity of Vitamin C quantity is less significant than slice method which is only 3.514%. Thus, shredding method produces small particle size of nutmeg pulp herbal tea powder and containing less Vitamin C.